Increasing Inclusion or Expanding Exclusion? How the Global Strategy to Include Refugees in National Education Systems Has Been Implemented in Lebanon - Kelcey, Jo; Chatila, Samira (Refuge)

(untitled) (Centre for Refugee Studies, York University, 2020)
The UNHCR strategy to include refugee students in host state education systems is intended to promote refugees’ access to quality education. However, numbers of out-of-school refugees far exceed the global average. To understand these persistent barriers, we examine how Lebanese teachers and school principals understand and enact inclusion for school-age Syrian refugees. We find that inclusion has been pursued in ways that reproduce education inequities in Lebanon. Our findings underscore the importance of account- ing for the internal complexities that shape the implementation and appropriation of policies within refugee host states and the ways in which these complexities interact with aid structures.